2017
DOI: 10.1038/s41598-017-08812-2
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the nutritive value of old bones in the diet of Bearded vultures Gypaetus barbatus

Abstract: Vultures are central-place foragers and need to optimize their foraging behaviour to offset travel costs by increasing their energy gain. This process is more obvious in certain vulture species that do not feed their young by regurgitation and so must carry food items back to the nest. The Bearded Vulture Gypaetus barbatus is the only species with a bone-diet based. We analysed the chemical composition of bones and the age-related changes in their nutritive value to assess the differences in energy content bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…By applying the criteria of Villa and Mahieu ( 31 ), the metapodials in Qesem appear to mainly register characteristics of a fresh fracture, with a preference to oblique angles, longitudinal delineations, and smooth surfaces. However, these bones can remain fresh over time, as they maintain not only their collagen in high proportions but also their nutritional values, such as fat and protein ( 32 ). In relation to this, the analysis of the fractures in the experimental series revealed that the angles, outlines, and surfaces were similar to those generated by fresh breakage even in weeks 6 to 9 in natural outdoor conditions (scenarios 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…By applying the criteria of Villa and Mahieu ( 31 ), the metapodials in Qesem appear to mainly register characteristics of a fresh fracture, with a preference to oblique angles, longitudinal delineations, and smooth surfaces. However, these bones can remain fresh over time, as they maintain not only their collagen in high proportions but also their nutritional values, such as fat and protein ( 32 ). In relation to this, the analysis of the fractures in the experimental series revealed that the angles, outlines, and surfaces were similar to those generated by fresh breakage even in weeks 6 to 9 in natural outdoor conditions (scenarios 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…This allows Bearded Vultures to profit the later daylight hours of convective updraughts to return to the nest or to search for a roosting site [ 15 ]. Moreover, the specific diet of this vulture—based mainly on the exploitation of bone remains, a resource which is preserved long time after a carcass has died—[ 29 , 55 ] releases it from interspecific competitive pressures, reasonably diminishing the impact of the optimal time to exploit carrion in the species daily feeding habits [ 22 ]. All these physiognomical and ecological attributes enable Bearded Vultures to solve the trade-off between the ideal feeding time and the availability of wind resource performing the furthest travelling distances during the afternoon, even though the greatest hourly distances travelled are achieved at mid-day.…”
Section: Discussionmentioning
confidence: 99%
“…The bearded vulture is a scavenger that collects bones from medium ungulates killed by carnivores or humans, or strips them from the carcasses of animals that have died from natural causes. The bone-based diet of the bearded vulture certainly has advantages over that of meat-eating scavengers because while the meat and soft tissues of a carcass decay quickly, bones and marrow are edible for longer periods: dry bones, for example, retain 90% of the protein found in fresh bones 5 . This means the bearded vulture can live in areas of low ungulate biomass, such as Tibet or the Himalayas, thanks to the longer-term benefit of carcasses 18 .…”
Section: Discussionmentioning
confidence: 99%